Coagulopathy and its associated factors among patients with bleeding history at the King Faisal medical complex in Taif City - Alhuthali, Hayaa; Al Shaibani, Ahmad; F. Ataya, Eman; Ahmed Al Salmi, Yasser; A. Alzahrani, Hind; Alsaeedi, Fouzeyyah A.; S. Al-Ghamdi, Abdullah; Alnemari, Reham; A. Alsaiari, Ahad; F. Gharib, Amal; Alrehaili, Amani A.; Bakhuraysah, Maha M. (Jour Med Resh and Health Sci, 2023)
Background Globally, around 26–45% of the population has a history of gum and nose bleeding, which may result from thrombocytopenia or factors deficiency. Saudi Arabia has a higher incidence of coagulopathy and frequent factor deficiencies. Methodology This study was conducted on 119 participants. Patients were recruited from King Faisal Medical Complex- Taif, Saudi Arabia, from February 2023 to April 2023. Blood was collected, and a complete blood count (CBC) test was performed to assess platelet number and prothrombin time (PT)/ international normalized ratio (INR) and activated partial thromboplastin time (APPT) was also done to evaluate coagulation factors. A mixing study was performed for participants with abnormal coagulation profiles. Result The study included 65 (55%) males and 54 (45%) females with an average age of 37 ± 19 years from Taif City. 68.1% (81/119) of the total participant had coagulopathy. 61.1% (73/199) had abnormal coagulation profiles, and only 6.7% (8/119) had thrombocytopenia. Individuals with prolonged coagulation time were categorized into three groups: 20.2% had a prolonged PT/INR and normal APTT, 17.6% (21/119) were with abnormal APPT and normal PT/INR and 23.5% (28/119) had abnormal PT/INR and APTT. Of the 73 study participants with prolonged coagulation time, 80.8% (59/73) and 19.2% (14/73) were due to factor deficiency and factors inhibitors, respectively. Multivariable analysis showed that individuals aged 46-65 (AOR = 7.11 (1.20: 41.99) or with a family history of coagulopathy (AOR= 19.45 (2.05: 184.24) were significantly associated with abnormal coagulation parameters. Conclusion This study indicated that coagulopathy is more frequent due to factor deficiencies in Saudi Arabia patients with a bleeding history. Also, it showed that chronic disorders are associated with bleeding disorders.